Patient perception on the effectiveness of shin pads in reducing the severity of injuries to the tibia following motorcycle accidents - Yeap, Joo Seng; Lim, J. L.; Pang, Toh Yen; Wong, Shaw Voon; Radin Sohadi, Radin Umar; Law, Teik Hua (2002)
This study aim to access the perception of motorcyclists on the effectiveness of shin pads in reducing the severity and preventing tibial injuries, and the likelihood of them wearing shin pads of proven effectiveness if these were available. 76 male motorcyclists (mean age 27.7±12.7 years) admitted to the hospital after their motorcycle accidents were interviewed after the interviewer had demonstrated to them the impact attenuating effects of the shin pads. 45 (59%) patients felt that the shin pads would be able to reduce the severity of tibial injuries. Patients aged ≤22 years were more likely to feel that the shin pads would not be able to reduce the severity of tibial injuries (p<0.008). 36 (48%) patients said that they would wear the shin pads. Patients aged above 22 years were more likely to agree to wear the shin pads than those below 22 years (63% compared to 35%) but this did not reach statistical significance (p<0.055). In conclusion, the group most at risk of injury is also the group least likely to feel that shin pads would help to reduce injuries, least likely to use and therefore benefit from the use of properly designed shin pads if they were to become available. This suggests that attention should not be focused on this method of injury prevention at the present moment.